Liolaemus Famatinae (Famatina Lizard). Parental Care. - Kass, Camila Alejandra (2023)
Liolaemus famatinae is small lizard known from FamatinaMountains in the La Rioja Province of western Argentina(Cei 1980. J. Herpetol. 14:57–64). It is a small-sized lizard thatruns agilely among the bushes during the sunniest hours. It inhabitshigh elevation grasslands, on stony often limonitic soils,with low vegetation and little is known about its reproductiveecology (Cei 1986. Reptiles del Centro, Centro-Oeste y Sur dela Argentina: Herpetofauna de las Zonas Áridas y Semiáridas.Mus. Reg. Sci. Nat. Torino, Turin, Italy. 527 pp.) except that theyare viviparous like other Liolaemus species living in high-elevationterrain (Cabrera and Monguillot 2007. Herpetol. Bull.101:34–35.). Viviparity seems to have emerged multiple timesamong squamate reptiles inhabiting cooler environmentsfound at high latitudes and elevations (Schulte et al. 2000. Biol.J. Linn. Soc. 69:75–102). Our observation is also congruent withthis reproductive pattern observed in most Liolaemus inhabitingharsh cold environments (Fernández et al. 2015. Herpetol.J. 25:101–108). Here, we report notes on clutch size and possibleparental care.